2013
DOI: 10.1111/nmo.12102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute peppermint oil administration on gastric sensorimotor function and nutrient tolerance in health

Abstract: Peppermint oil reduces IGP, proximal phasic contractility, and appetite, with negligible effects on gastric sensitivity, tone, accommodation, and nutrient tolerance in health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 41 publications
(96 reference statements)
1
47
1
2
Order By: Relevance
“…These observations confirm that duodenal nutrients can induce or enhance gastric relaxation, but do not reveal how much this contributes to the GA reflex under physiological circumstances. In the present study, we used IGP to quantify changes in gastric tone, and similar to previous studies, we observed a pressure drop upon intragastric nutrient infusion, representing gastric relaxation. When the passage of nutrients to the duodenum was blocked by a pyloric balloon, the magnitude of the IGP drop was significantly inhibited.…”
Section: Discussionsupporting
confidence: 75%
“…These observations confirm that duodenal nutrients can induce or enhance gastric relaxation, but do not reveal how much this contributes to the GA reflex under physiological circumstances. In the present study, we used IGP to quantify changes in gastric tone, and similar to previous studies, we observed a pressure drop upon intragastric nutrient infusion, representing gastric relaxation. When the passage of nutrients to the duodenum was blocked by a pyloric balloon, the magnitude of the IGP drop was significantly inhibited.…”
Section: Discussionsupporting
confidence: 75%
“…In healthy volunteers, peppermint oil has been shown to reduce gastric and duodenal motility, but not gastric satiation, postprandial symptom scores, or accommodation as measured by barostat, in response to a nutrient drink meal. 34 Caraway oil has also been associated with inhibition of antroduodenal motility upon intra-duodenal infusion in healthy subjects. 35 A randomized, controlled trial of two combination of peppermint/caraway oil (90 mg/50 mg vs 36 mg/ 20 mg) in 223 patients with non-ulcer dyspepsia reported reduction in pain scores for both preparations.…”
Section: Peppermint Oil Caraway Oilmentioning
confidence: 99%
“…Peppermint oil (PO; Mentha piperita L), a natural oil obtained by steam distilling fresh leaves of the peppermint plant, is a perennial herb commonly found across North America and Europe. PO been associated with reduced GI spasms and gastric pressure, decreased frequency and severity of abdominal pain, stimulated bile flow, and antibacterial properties . The antispasmodic and GI‐soothing effects of PO have made it a common herb in complementary and alternative medicine for ailments that include irritable bowel syndrome (IBS), dyspepsia, nausea, and general abdominal discomfort and cramping .…”
Section: Methodsmentioning
confidence: 99%